Labour migration in Malaysia and Spain : markets, citizenship and rights - Garcés-Mascareñas, Blanca (IMISCOE research., 2012)
State regulation of labour migration is confronted with a double paradox. First, while markets require a policy of open borders to fulfill demands for migrant workers, the boundaries of citizenship impose some degree of closure to the outside. Second, while the exclusivity of citizenship requires closed membership, civil and human rights undermine the state's capacity to exclude foreigners once they are in the country. By considering how Malaysia and Spain have responded to the demand for foreign labour, this book analyses what may be identified as the trilemma between markets, citizenship and rights.